Terror in France: the rise of Jihad in the West - Kepel, Gilles (Princeton studies in Muslim politics, 2017)
In November 2015, ISIS terrorists massacred scores of people in Paris with coordinated attacks on the Bataclan concert hall, cafés and restaurants, and the national sports stadium. On Bastille Day in 2016, an ISIS sympathizer drove a truck into crowds of vacationers at the beaches of Nice, and two weeks later an elderly French priest was murdered during morning Mass by two ISIS militants. Here is Gilles Kepel's explosive account of the radicalization of a segment of Muslim youth that led to those attacks - and of the failure of governments in France and across Europe to address it. It is a book everyone in the West must read. Terror in France shows how these atrocities represent a paroxysm of violence that has long been building. The turning point was in 2005, when the worst riots in modern French history erupted in the poor, largely Muslim suburbs of Paris after the accidental deaths of two boys who had been running from the police. The unrest - or "French intifada"--Crystallized a new consciousness among young French Muslims. Some have fallen prey to the allure of "war of civilizations" rhetoric in ways never imagined by their parents and grandparents. This is the highly anticipated English edition of Kepel's sensational French bestseller, first published shortly after the Paris attacks. Now fully updated to reflect the latest developments and featuring a new introduction by the author, Terror in France reveals the truth about a virulent new wave of jihadism that has Europe as its main target. Its aim is to divide European societies from within by instilling fear, provoking backlash, and achieving the ISIS dream - shared by Europe's Far Right - of separating Europe's growing Muslim minority community from the rest of its citizens. --